Introduction To Engineering Design And Problem Solving - Arvid R.Eide, Roland D.Jenison (Mc Graw Hill, 1998)
This book is conveniently divided into two major sections. The first, an introduction to engineering begins with a descriptions and breakdown of the engineering profession